(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Tissue engineering is a rapidly progressing field of science that provided the surgery with better options for treatment; lip has unique anatomy, shape and functions. Large lip defect is one of the great challenges for plastic surgeons, the gold standard option is autologous tissue replacement with drawbacks of donor site morbidity and suboptimal outcomes, tissue engineering came up with new option for partial thickness defect to address the skin-vermilion loss as a composite graft but not the orbicularis oris muscle, before preceding for tissue engineered orbicularis oris muscle it is wise to study the biomechanical properties of the lip and then matching the measures with tissue engineered product as basic biomechanical properties affect the lip shape and functions. Keywords :Biomechanics, stiffness, tissue engineering, lip, orbicularis oris, vermilion reconstruction, perioral dynamics